Fabrication and characterization of inkjet-printed interdigitated electrodes for non-faradaic electrochemical detection of uromodulin in urine - Kunj Vora; Norbert Kordas; Karsten Seidl (Sensing and Bio-Sensing Research)
This work describes the simulation, design, and fabrication of an inkjet-printed impedance biosensor for uromodulin which is a urine biomarker for kidney disease. The interdigitated electrodes (IDE) were fabricated through inkjet printing of silver ink on polyethylene terephthalate (PET) substrate and subsequently passivated with SU-8 for non-faradaic measurements. We functionalized the passivated IDE with biotin-streptavidin complex and uromodulin antibody to detect uromodulin (6.75 μg/ml-100 μg/ml). The measured impedance due to uromodulin immobilized from artificial urine samples showed a 27.4 % change in impedance magnitude per μg/ml of uromodulin at 150 Hz (log scale). The limit of detection achieved is 25 ng/ml. The sensor demonstrated specificity to uromodulin when measured against albumin, which is another protein biomarker present in the urine. These results highlight the possibility of implementing non-faradaic impedance measurements using a passivated IDE as the sensor element. It also promotes the sensor fabrication method of inkjet printing. The sensor concept shows the implementation potential of IDE as a single-use-sensor for point-of-care applications.